Synthesis and spectroscopic characterization of 5-diaminomethylidene barbiturates - Figueroa-Villar José D.; Clemente Fábio C.; Silva Ana C. C. da (Journal of the Brazilian Chemical Society, 2001)
The reaction of amines with dithiocyclohexylidenes is a general reaction for the synthesis of diaminomethylidene barbiturates. When diamines of the type H2N-(CH2)n-NH 2 are used as nucleophiles bicyclic compounds are the major reaction products, with yields increasing as n decreases, n = 2, 3, 4. When n = 6, macrocyclic compounds, novel 18 and 27 member rings, are obtained in very good yields. The ¹H and 13C NMR assignment for all products is discussed.